Sisa makanan dan faktor determinan yang memengaruhi pasien rawat inap di Rumah Sakit Islam PKU Muhammadiyah Tegal - Ansari, Muhammad Ridwan; Nuramalah, Rizqi; Maharani, Santi Diah; Fitrianingsih, Desi; Assamlawy, Ibnu Mu’thi; Ardiningrum, Berliani Putri; Chrisiyanti, Anis (Jurnal Gizi Klinik Indonesia, 2025)
Hospital food waste and its determinant factor among inpatients at PKU Muhammadiyah Tegal HospitalBackground: The amount of food waste reflects patients’ acceptance of the food served in the hospital and is used to assess food service quality. Patient satisfaction and compliance with the hospital’s food therapy will speed up the patient’s recovery and prevent malnutrition.Objective: This study aims to assess the level of food waste as well as the factors that influence food waste among patients at PKU Muhammadiyah Hospital Tegal.Methods: A descriptive cross-sectional research design was employed, involving 68 respondents purposively selected from PKU Muhammadiyah Hospital in October 2024. The percentage of food waste was estimated using visual comstock observation with six standards over 3 days of the menu cycle at the hospital. Ten aspects of food service satisfaction data were collected through interviews using standard questionnaires. Descriptive data analysis and an independent t-test were used to determine the difference in satisfaction levels between groups of patients with low food waste (<25%) and high food waste (>25%).Results: The average food waste rate was determined at 27%. Patients in the internal medicine ward contributed the greatest to food waste, accounting for 46.7% compared to other wards. Vegetable meals account for 35.5% of all food waste. Patients with low food waste reported considerably higher satisfaction scores than patients with high food waste, particularly in terms of meal appearance, cleanliness of dining utensils, and staff appearance.Conclusions: The aspects of food appearance, cleanliness of dining utensils, and staff appearance significantly influence the leftover food served by the hospital.